Preparations and evalution of goat milk yoghurt whith jellies pineapple (Ananas comosus) and noni (Morinda citrifolia) (Research, Society and Development, 2020)
The objective was to prepare goat's milk yogurt with the addition of pineapple (Ananas comosus) and noni (Morinda citrifolia) jams and to evaluate the product's physical-chemical, microbiological and sensory parameters. Five treatments of goat's milk yogurt were developed with different concentrations of pineapple and noni jellies (0, 0.5, 1.25, 2.5 and 5%). In the treatments, the physical-chemical composition (humidity, ash, lactose, acidity, pH, fat, protein), microbiological (coliforms at 45ºC, mesophiles, psychrotrophic, salmonella spp., And positive coagulase staphylococcus) were determined, and in relation to the analyzes sensory, 20 (twenty) trained tasters performed tests such as: quantitative descriptive analysis (QDA), purchase intention and acceptance test. There was no significant difference (p